The areas of teacher training And the educational task - Burga Gutiérrez, Rosa María (2023)
The paper develops an analysis of teacher training áreas and the educational task. In this regard, initially a few ideas about challeges today´s teacher training were developed, thereafter teacher training is analized according three areas: pedagogical, disciplinary and technological.